A ISLAMIC SOCIAL REPORTING: MENGUJI PENGARUH DARI MAQASHID SHARIA INDEX, SHARIA SUPERVISORY BOARD, MEDIA EXPOSURE, DAN COMPANY SIZE DI PERBANKAN SYARIAH INDONESIA - Aji, Nur Prasetyo; Pamungkas, Mahendra; Dewi, Indah Permata; Ulynnuha, Ovi Itsnaini (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
The growth of Islamic banking, issues related to sustainable business practices and adherence to Sharia principles are increasingly coming into focus. In order to understand the dynamics of social reporting in the context of Islamic banking in Indonesia, this study aims to analyze the influence of Maqashid Sharia Index, Sharia Supervisor Board, Media Exposure, and Company Size on Islamic Social Reporting in Indonesian Islamic banks listed on the Indonesia Stock Exchange from 2018 to 2020. The study employed purposive sampling, and 39 companies met the criteria as the unit of observation. The analysis was conducted using multiple linear regression. The results provide empirical evidence that Sharia Supervisor Board, Media Exposure, and Company Size have a significant influence on Islamic Social Reporting, while Maqashid Sharia Index does not have a significant impact on Islamic Social Reporting.